2012
DOI: 10.1007/978-3-642-33454-2_59
|View full text |Cite
|
Sign up to set email alerts
|

Non-local Robust Detection of DTI White Matter Differences with Small Databases

Abstract: Abstract. Diffusion imaging, through the study of water diffusion, allows for the characterization of brain white matter, both at the population and individual level. In recent years, it has been employed to detect brain abnormalities in patients suffering from a disease, e.g. from multiple sclerosis (MS). State-of-the-art methods usually utilize a database of matched (age, sex, ...) controls, registered onto a template, to test for differences in the patient white matter. Such approaches however suffer from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, the over-estimation of extrema was much smaller for EZ-MAP/DisCo-Z relative to IDS/LOO across all non-normal distributions, suggesting that the correction applied by both algorithms is more effective than not applying any correction at all. Recently, Gaussian error propagation (Gebhard et al 2015; Shaker et al 2017) and a non-local means framework (Commowick and Stamm 2012) have been suggested as other corrective method for approximating SSA across multiple sample sizes and initial distributions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the over-estimation of extrema was much smaller for EZ-MAP/DisCo-Z relative to IDS/LOO across all non-normal distributions, suggesting that the correction applied by both algorithms is more effective than not applying any correction at all. Recently, Gaussian error propagation (Gebhard et al 2015; Shaker et al 2017) and a non-local means framework (Commowick and Stamm 2012) have been suggested as other corrective method for approximating SSA across multiple sample sizes and initial distributions.…”
Section: Discussionmentioning
confidence: 99%
“…| S | = 11, including one target noisy image and ten co-denoising images. σ̂ i was estimated based on a cubic volume (radius = 2) centered at x i , similar to the methods described in [2, 29]. …”
Section: Resultsmentioning
confidence: 99%
“…Coupé et al 27. suggested to set , where is the cardinality of , β is a constant that is set to 1, is an estimate of the standard deviation of the noise at x i , which is spatial-adaptively estimated28. In our case, we set block radius d  = 1 voxel and search radius m  = 2 voxels.…”
Section: Methodsmentioning
confidence: 99%